2019
DOI: 10.1111/apm.12923
|View full text |Cite
|
Sign up to set email alerts
|

Mapping bacterial biofilms on recovered orthopaedic implants by a novel agar candle dip method

Abstract: Dusane DH. Mapping bacterial biofilms on recovered orthopaedic implants by a novel agar candle dip method. APMIS 2019; 127: 123-130.While the detrimental effects of periprosthetic joint infections (PJIs) are well known, the process of biofilm formation on orthopaedic hardware is unclear. Previous work has shown that encasement of explant hardware in agar can aid in identifying biofilms. This study tested the utility of agar 'candle dip' method in detecting and mapping the location of biofilm on infected orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…4a-d) and illustrates the importance of adequate spatial coverage within a periprosthetic joint or other infected surgical sites. Nevertheless, our in vitro data as well as those found clinically (Morgenstern et al, 2018;Ciofu et al, 2017), and data from other in vitro studies (Howlin et al, 2015(Howlin et al, , 2017Laycock et al, 2018;Knecht et al, 2018) support the use of ALCS-B as an effective means of releasing antibiotic to prevent biofilm spread and kill pre-grown bacterial biofilms.…”
Section: Discussionsupporting
confidence: 77%
“…4a-d) and illustrates the importance of adequate spatial coverage within a periprosthetic joint or other infected surgical sites. Nevertheless, our in vitro data as well as those found clinically (Morgenstern et al, 2018;Ciofu et al, 2017), and data from other in vitro studies (Howlin et al, 2015(Howlin et al, , 2017Laycock et al, 2018;Knecht et al, 2018) support the use of ALCS-B as an effective means of releasing antibiotic to prevent biofilm spread and kill pre-grown bacterial biofilms.…”
Section: Discussionsupporting
confidence: 77%
“…The satisfying outcome of the aforementioned “agar candle dip” method ( 9 ) implies that culture on explant components may be a useful strategy to identify FDRI-related pathogens because of the possibility of bacterial biofilms attached to the implant surfaces. We believe that ISC primarily has 3 advantages compared with TSC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study reported using a novel “agar candle dip” method to map the bacterial biofilms on recovered orthopedic implants ( 9 ), which showed promise in growing bacteria directly from the implants. These findings suggest that culturing directly from implant surfaces may be an effective method for bacteria detection as there may exist bacterial biofilms attached to the implant surfaces.…”
mentioning
confidence: 99%
“…The implant must then be submerged in cooled agar and placed in a new container to be incubated for 7 days. In this study, the agar began to noticeably dry out after a 24‐h incubation period; therefore, the authors incorporated an agar replenishment step every 24 h for 7 days in their methodology [58].…”
Section: Novel Diagnostic Technologies Limited To Researchmentioning
confidence: 99%
“…This method can have a lot of colony growth in the growth media. Also, research with a larger quantity of patient samples is necessary prior to clinical use [58].…”
Section: Novel Diagnostic Technologies Limited To Researchmentioning
confidence: 99%